Podredno izraženi protivnost in pojasnjevalnost - Gabrovšek, Dejan (Jezik in slovstvo, 2018)
The aim of the contribution is to explore the function of subordinate conjunctions that express contrast and clarification. This is associated with different typologies of embedded clauses and the attention paid to lexical and semantic structures. The first part refers to Slovenska slovnica and contemporary literature, while the second part analyses the usage of conjunctive elements, predominantly focusing on transformations into coordinate clauses.
Keywords: podredje; pojasnjevalnost; priredje; protivnost; slovenščina; vezniška beseda